Language Analysis of Science and Technology Textbook in Nepal: A Semiotic Perspective - Parajuli, Dilu Ram (Gipan, 2024)
This article has analyzed the semiotic aspects of grade 10 Science and Technology subjects’ textbook implemented in Nepal. The main objective of this study was to explore the kind of figures, pictures, symbols, graphs and other signs used in science textbook. It examined how the figures and signs used in the book effect on science learning. It has been carried out in a qualitative design because it is developed on critical logic and argumentative analysis. Theoretically, this work believes on Peirce’s semiotics. Figures, pictures, symbols, graphs and other kind of signs used in this subjects’ textbook act as data in this study. The meaning-making process includes qualitative and critical analysis. It combines signs from several contexts, meaning, abbreviation including the verbal semantics of speech, and the operational system. And, its result was summarized in overall synopsis of content related aspect and pedagogical techniques and practices correspondence with relevancy and misconception. The result show that the use of visual materials, such as graphs, symbol, pictures, figure, etc. in science textbooks can serve as semiotic signs that induce argumentative reasoning and contribute to the structure of scientific arguments in science classroom. It provides good insights into the representation of multiple mode of representation, scientific influences, and the use of visual materials to enhance scientific literacy however it needs to uplift.